Effect of Daily Intake of Heat-Killed Lactobacillus plantarum HOKKAIDO on Immunocompetence: A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group Study - Nishihira, Jun; Haseda, Akane; Nishimura, Mie; Sugawara, Miwako; Kudo, Masafumi; Nakagawa, Ryoji (Bioactive compounds in health and disease, 2020)
Background: Consumption of Lactobacillus plantarum HOKKAIDO (HOKKAIDO strain) reportedly increases immunocompetence. However, the concentration of viable bacteria and the type of food they can be incorporated into limits their consumption. The study aims to demonstrate the effect of daily intake of the heat-killed L. plantarum HOKKAIDO strain (HK-HOKKAIDO strain; 5 × 1010 colony-forming units/day) by healthy subjects with low natural killer (NK) cell activity for 8 weeks.Method: In this randomized, double-blind, placebo-controlled, parallel-group study, 70 healthy Japanese subjects who showed relatively low NK cell activity were recruited and randomly assigned to the HK-HOKKAIDO strain or placebo group. All subjects ingested one capsule per day for 8 weeks. We conducted medical interviews and performed body composition measurements, vital sign examinations, and blood sampling at weeks 0 (baseline), 4, and 8, and we collected salivary samples at weeks 0 and 8. In addition, the frequency and severity of cold symptoms in the subjects were recorded daily during the intake period.Results: Intake of the HK-HOKKAIDO strain did not increase the NK cell activity or immunity marker levels, including those of immunoglobulin, leukocyte fraction, and salivary secretory immunoglobulin A. However, the frequency and severity of the common cold symptoms were significantly reduced after the daily consumption of the HK-HOKKAIDO strain.Conclusions: The results showed that HK-HOKKAIDO strain administration can decrease the frequency and severity of common cold symptoms in healthy subjects. Our findings support the use of the HK-HOKKAIDO strain as a functional food with health benefits.Clinical trial registration: UMIN000034822